Analyzing the soil loss estimating by erosion processes in monitoring plots using erosion pins on rural properties in the State of Sao Paulo - Baldassarini, Jessica de Sousa [UNESP]; Rodrigues Nunes, Joao Osvaldo [UNESP] (Revues Org, 2018)
The pursuit for understanding the dynamics involved soil loss by erosion processes, aiming at its measurement and conservation management, is taking space in the scientific world due to socioeconomic and environmental problems resulting from this type of degradation. For that we are discussing the importance of considering the natural aspects what promote soil loss and agricultural practices. The study was conducted in two farms in the State of Sao Paulo-Brazil, located in the municipality of Getulina, intended for beef cattle, and the second in Veracruz, for the coffee production. The soil losses were estimated by monitoring plots with erosion pins, registering the monthly variations for a year. These records were compared with daily precipitation data and with the vegetation cover percentage present within the plots. Analyzing the results was identified the largest annual soil loss in Veracruz, estimated at 691 T/ha/year. This soil loss is associated with the greatest precipitation record in Veracruz, as well as with the largest vegetation cover percentage variation over the months, associated with the coffee plantation in formation, which results in a large exposed soil portion. In addition, and as conclusion, the morphological and textural features indicate a tendency to compaction, especially with intensive use of farm machines, with strong textural change, which helps with less porosity and permeability, and with a surface horizon cohesive, easily take by little runoff.
Keywords: erosion; soil loss; experimental plots